The effect of shoe type on gait in forefoot strike runners during a 50-km run - Mark E. Kasmer; Nicholas C. Ketchum; Xue-Cheng Liu (Elsevier, 2014)
Purpose: To observe the relative change in foot-strike pattern, pressure characteristics, surface electromyography (sEMG) recordings, and stride characteristics in forefoot strike runners wearing both minimalist and traditional shoes during a 50-km run. Methods: Four experienced minimalist runners were enrolled in this study. Each runner ran a 50-km simulated run in both minimalist shoes and traditional shoes. Pressure data, sEMG recordings, and limited 3D motion capture data were collected during the initial 0.8 km and final 0.8 km for each trial. Results: Three runners in the traditional shoe type condition and one runner in the minimalist shoe type condition demonstrated a more posterior initial contact area (midfoot strike (MFS) pattern) after the 50-km run, which was supported by increased activity of the tibialis anterior in the pre-contact phase (as per root mean square (RMS) values). In addition, in both pre- and post-run conditions, there were increased peak pressures in the minimalist shoe type, specifically in the medial forefoot. Muscle fatigue as defined by a decreased median frequency observed in isometric, constant force contractions did not correspond with our hypothesis in relation to the observed foot strike change pattern. Finally, step rate increased and step length decreased after the 50-km run in both shoe type conditions. Conclusion: More runners adopted a more posterior initial contact area after the 50-km run in the traditional shoe type than in the minimalist shoe type. The runners who adopted a more posterior initial contact area were more closely associated with an increased median frequency of the medial gastrocnemius, which suggests there may be a change in motor unit recruitment pattern during long-distance, sustained velocity running. The increased peak pressures observed in the medial forefoot in the minimalist shoe type may predispose to metatarsal stress fractures in the setting of improper training.